Respuesta :

3x + 12 = 3

(multiply 3 by the variables in the parentheses)

3x + 12 = 3

add 12 to each side

3x = 15

divide each side by 3

X=5

In order to solve this, start by distributing the 3.

Essentially, we multiplying each value inside the parenthesis by 3, to get:

3x + 12 = 3

Next, subtract 12 on both sides:

3x + 12 - 12 = 3 - 12

12 - 12 = 0
3 - 12 = -9

So:

3x = -9

The last step here is to divide both sides by 3:

3x ÷ 3 = -9 ÷ 3

3 • X ÷ 3 = X
-9 ÷ 3 = -3

So, long story short, X = -3